Investigation of Antibacterial Activity of Biosynthetic Copper Oxide Nanoparticles - Karam Khan Azizi; Usefzay Obaidullah; Gulaqa Anwari (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
The present study aims to investigate the antibacterial activity of copper oxide nanoparticles synthesized by the gram-negative bacterium Escherichia coli. Biosynthetic CuONPs produced were tested on two pathogenic model bacteria, such as Pseudomonas aeruginosa (PTTC 1707) and Bacillus cereus (PTTC1154). The antibacterial effect of the mentioned nanoparticles was investigated using two methods of determining (MIC and well diffusion). Dilution series were used to determine the zone of no growth in the well diffusion method from 160 to 5 μg/mL, and the diameters of the formed zones were measured in milliliters. Also, to determine the minimum growth inhibitory concentration (MIC) of each bacterium, a series of 10 tubes with dilutions of copper oxide nanoparticles from 320 to 0.62 μg/mL was used. The results of the findings indicated that these nanoparticles showed significant antibacterial activity on the tested strains, such that they prevented the growth of bacteria at very low concentrations. The minimum inhibitory concentration (MIC) of copper oxide nanoparticles for both bacteria (Bacillus cereus) and (Pseudomonas aeruginosa) was calculated to be 10 and 5 micrograms ml, respectively. The diameters of the halos formed by these two bacteria were also calculated to be 17 and 20 mm, respectively.